2002
DOI: 10.1021/ma0119272
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric and Polymeric Phenothiazine Photosensitizers for Photoinitiated Cationic Polymerization

Abstract: The syntheses of several phenothiazine compounds bearing cationically polymerizable vinyl, vinyl ether and epoxide groups are described. These monomers were rapidly and efficiently polymerized or copolymerized by UV irradiation in the presence of onium salt photoinitiators. In addition, the monomers simultaneously function as efficient photosensitizers for the photolysis of the onium salts. In this article, the use of these polymerizable photosensitizers for the photopolymerizations of epoxide and vinyl ether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…[71] Most of these studies were focused on cycloaliphatic epoxides which are the most utilized monomers because of their superior reactivity. The addition of a comonomer was shown to speed up the UVcuring process and to lead to a more complete polymerization, especially for aromatic diepoxides.…”
Section: Photoinitiated Cationic Polymerizationmentioning
confidence: 99%
“…[71] Most of these studies were focused on cycloaliphatic epoxides which are the most utilized monomers because of their superior reactivity. The addition of a comonomer was shown to speed up the UVcuring process and to lead to a more complete polymerization, especially for aromatic diepoxides.…”
Section: Photoinitiated Cationic Polymerizationmentioning
confidence: 99%
“…Research has been reported by several groups including Crivello and co-workers, Yagci and co-workers, and Jacques Lalevée and co-workers. [19][20][21][22][23][24][25][26][27] Photolysis of onium salts is photosensitized by various monomeric and polymeric compounds containing the carbazole, triphenylamine and phenothiazine.…”
Section: -15mentioning
confidence: 99%
“…The sensitizer, Rose Bengal (RB) and the initiator Nphenylglycine (NPG) (Kanto Chemical) were used as received. 3,3 -Carbonylbis(7-diethylaminocoumarin) (KC, Kodak) and diphenyliodonium hexafluorophosphate (DPI, AVOCADO Research Chemicals Ltd.) were used as PS and PI, respectively, to produce both cationic and radical species [22,23]. Visible photo-initiator, Irgacure 784 [bis(η 5 -cyclopentadienyl)bis[2,6-difluoro-3-(1H-pyrrol-1-y)]-titanium, Ciba-Geigy] to produce only radical species was also used.…”
Section: Composition Of Photo-initiator System and Recording Solutionmentioning
confidence: 99%